A rare case of heterotopic pregnancy: an avalanche of catastrophe - Bhattacharya, Rangan; Raut, Rohini; Kumari, Beena; Hojai, D. C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
An ectopic pregnancy is the development of an embryo outside the uterus, a major cause of maternal morbidity and mortality. Heterotopic pregnancy is when an intrauterine implanted embryo develops simultaneously along with an extra uterine implantation. With rising incidence of assisted reproductive technology (ART), incidence of ectopic pregnancy is on a rise. We report a case of an elderly patient, conceived by in vitro fertilization and embryo transfer (IVF-ET), who had a catastrophe of events following conception, where she had an intrauterine twin gestation and an ectopic gestation in the left fallopian tube. She presented with vomiting and on ultrasound scan, we found a twin intra uterine gestation, with demise of one twin with no sign of ectopic implantation. Initially we decided to continue pregnancy. However, she had persistent spotting per vagina, and on a repeat ultrasound scan there was intrauterine demise of the other foetus also. Her uterus was then evacuated under anaesthesia. Post operatively, she became hemodynamic ally unstable and ultrasound was inconclusive of the cause. So, we subjected her to an MRI which showed a left adnexal ruptured ectopic pregnancy with hemoperitoneum. She was immediately taken up for exploratory laparotomy and left salpingectomy was done hemoperitoneum evacuated. Due to timely intervention and use of advanced techniques for diagnosis, she recovered successfully. Thus, heterotopic pregnancy can be a rare, life threatening complication of IVF, a vigilant eye and not shying away from the use of novel and advanced techniques for diagnosis, can help in early diagnosis and timely intervention and thus prove to be lifesaving.